Trauma Care Manual - Greaves, Ian; Porter, Keith M.; Garner, Jeff (CRC Press, 2022)
The Trauma Care Manual, Third edition is the definitive evidence-based manual of best trauma practice. Now in its third edition, this valuable book continues to provide clear practical guidelines for the management of victims of major trauma. New coverage includes chapters on abdominal and urological trauma, as well as trauma in the obese patient. Also included is coverage of pre-hospital management; trauma centres, systems & teams; modern trauma resuscitation; trauma physiology & metabolism; damage control surgery. Written by members of Trauma Care, this book offers a nationally accepted set of standards for good practice.